2020
DOI: 10.5194/acp-20-7509-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ship emissions on air quality and human health in the Gothenburg area – Part 1: 2012 emissions

Abstract: Abstract. Ship emissions in and around ports are of interest for urban air quality management in many harbour cities. We investigated the impact of regional and local ship emissions on urban air quality for 2012 conditions in the city of Gothenburg, Sweden, the largest cargo port in Scandinavia. In order to assess the effects of ship emissions, a coupled regional- and local-scale model system has been set up using ship emissions in the Baltic Sea and the North Sea as well as in and around the port of Gothenbur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
2
55
1
Order By: Relevance
“…Also, different methods of health impact assessment used in these studies are briefly reviewed. In Tang et al (2020) we discuss that shipping in Gothenburg in 2012 was a significant source of air pollution, contributing with 35 % and 12.5 % to the annual exposure to NO2 and PM2.5, respectively, and that the regional shipping outside the city was responsible for 20 % and 10 % of the NO2 and PM2.5 exposure, contributing more than the local shipping in and around the harbours. According to the study of Karl et al (2019a), the introduction of the SECA with a fuel Sulphur limit of 0.1 % decreased the exposure to PM2.5 at the Swedish West coast by approximately 35 %.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Also, different methods of health impact assessment used in these studies are briefly reviewed. In Tang et al (2020) we discuss that shipping in Gothenburg in 2012 was a significant source of air pollution, contributing with 35 % and 12.5 % to the annual exposure to NO2 and PM2.5, respectively, and that the regional shipping outside the city was responsible for 20 % and 10 % of the NO2 and PM2.5 exposure, contributing more than the local shipping in and around the harbours. According to the study of Karl et al (2019a), the introduction of the SECA with a fuel Sulphur limit of 0.1 % decreased the exposure to PM2.5 at the Swedish West coast by approximately 35 %.…”
Section: Introductionmentioning
confidence: 96%
“…However, the abatement measures considered as well as the methods used differ from our approach. The first part of our study (Tang et al, 2020) gives a brief overview of previous studies about impacts of shipping emissions on air quality and health at the Swedish west coast. It provides discussion on how the legislation changed between the base year used in our study (2012) and the situation today.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with no exceedances of measured PM2.5 limit values in 2012 in any of the domains and large negative BIAS for PM2.5 due to underestimated regional background concentrations, we decided not to show the total air quality and contribution of shipping to PM2.5 here and in the exposure evaluation. Besides this, a study in preparation (Tang et al 2019) for the city of Gothenburg, showed a small impact of local shipping to PM2.5 contribution (0.07 µg m -³) but higher PM2.5 contribution from regional shipping (0.49 µg m -³).…”
Section: Predicted Concentrations and Impact Of Shipping On No2 In 2012mentioning
confidence: 88%
“…The same regional CTM system was used in a study in preparation (Tang et al, 2019) to perform local CTM simulations in the Gothenburg area with the chemistry transport module of TAPM but with a different preparation of boundary concentrations from CMAQ: TAPM allows just 1-d boundary concentration fields with time being the only variable, and therefore the TAPM boundary concentrations were calculated using horizontal wind components on each of the four lateral boundaries for weighting the boundary concentrations. Matthias et al (2018) have discussed the necessity to utilize emission data in high spatial and temporal resolution on a coordinate grid that is in agreement with the CTM grid, due to emission data being probably the most important input for chemistry transport model (CTM) systems.…”
Section: Boundary Conditionsmentioning
confidence: 99%